Sculpture / Installations. - Brown University, Providence (Providence : Brown University, 1983)
Vidaver Cohen, Deborah ; Coogan, Jay ; Schiff, Jeffrey ; Wiener, Daniel
Sculpture / Installations, Bell Gallery, List Art Center, Brown University, Providence, January 7 - February 2, 1983
boek